2017
DOI: 10.1021/acs.molpharmaceut.6b01088
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of an EP67-Conjugated CTL Peptide Vaccine in Nanoscale Biodegradable Particles Increases the Efficacy of Respiratory Immunization and Affects the Magnitude and Memory Subsets of Vaccine-Generated Mucosal and Systemic CD8+ T Cells in a Diameter-Dependent Manner

Abstract: The diameter of biodegradable particles used to co-encapsulate immunostimulants and subunit vaccines affects the magnitude of memory CD8+ T cells generated by systemic immunization. Possible effects on the magnitude of CD8+ T cells generated by mucosal immunization or memory subsets that potentially correlate more strongly with protection against certain pathogens, however, are unknown. In this study, we conjugated our novel host-derived mucosal immunostimulant, EP67, to the protective MCMV CTL epitope, pp89, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 79 publications
0
10
0
Order By: Relevance
“…For example, Montanide ISA 51 in combination with a cocktail of HIV-derived peptide antigens (containing a mixture of peptide specifying B- and T-cell epitopes) enhanced the immunogenicity of the antigenic peptide [ 50 ]. The epitopes can also be fused with adjuvant proteins [e.g., toll-like receptor (TLR) ligands] which can be encapsulated or displayed on the surface of nanoparticles [e.g., poly lactic- co -glycolic acid (PLGA)] to elicit sustained T-cell responses and increase long term protection [ 8 , 51 , 52 ].…”
Section: Design Of Multi-epitope Peptide-based Vaccinesmentioning
confidence: 99%
“…For example, Montanide ISA 51 in combination with a cocktail of HIV-derived peptide antigens (containing a mixture of peptide specifying B- and T-cell epitopes) enhanced the immunogenicity of the antigenic peptide [ 50 ]. The epitopes can also be fused with adjuvant proteins [e.g., toll-like receptor (TLR) ligands] which can be encapsulated or displayed on the surface of nanoparticles [e.g., poly lactic- co -glycolic acid (PLGA)] to elicit sustained T-cell responses and increase long term protection [ 8 , 51 , 52 ].…”
Section: Design Of Multi-epitope Peptide-based Vaccinesmentioning
confidence: 99%
“…In addition, 357‐nm PLGA particles with co‐encapsulated poly(I:C) and OVA induced a stronger OVA‐specific IgG response than did 17‐μm particles with the same composition . Furthermore, the frequency of murine cytomegalovirus‐specific cytotoxic T lymphocytes was significantly higher in both mucosal and systemic tissues of mice immunized intratracheally with 350‐nm PLGA nanoparticles with encapsulated peptide vaccine than after the immunization with 5.4‐μm PLGA microparticles . Although the optimal size of silica nanoparticles for the induction of immune response was smaller than that used in other vaccines, these previous reports suggested that 100‐500‐nm particles can be adapted for vaccine preparations.…”
Section: Discussionmentioning
confidence: 95%
“…Because particle size influences the competence of immune responses induced by vaccination, it must be considered when vaccine formulations are intended for intranasal immunization . It has been frequently reported that particle size influences immune responses . With regard to vaccine Ags, it has been noted that only particles in the nanometre range, that is of the size of viruses, can reach lymph nodes and directly interact with B cells, inducing potent immune responses .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations